Large Magnetoresistance in Silicon at Room Temperature Induced by Onsite Coulomb Interaction. (31st July 2017) - Luo, Zhaochu; Piao, Hong‐Guang; Brooks, Andrew V.; Wang, Xiaofeng; Chen, Jiaojiao; Xiong, Chengyue; Yang, Fuhua; Wang, Xiangrong; Zhang, Xiao‐Guang; Zhang, Xiaozhong
Abstract : Magnetoresistance (MR), as a key property in magnetic‐field sensing and magnetic storage, has been a long‐term focus. In particular in silicon, which is the mainstream semiconductor of information technology, the MR phenomenon has attracted a lot of attention because of its fundamental interest and broad application potential. Here, a large MR in silicon, which is associated with impurity onsite Coulomb interaction and space charge limited current (SCLC), is observed at room temperature. In the presence of SCLC, delocalization of electrons in doubly occupied traps with a strong onsite Coulomb interaction leads to an S‐shape negative differential conductance (SNDC). A large room temperature MR (>10 3 % at 0.05 T) appears around the SNDC region. These findings will help to design high‐performance silicon‐based magnetic device (e.g., magnetic switch devices, magnetic logic devices) and pave the way for magnetoelectronics in silicon. Abstract : In the presence of space charge limited current effect, delocalization of electrons in doubly occupied traps with a strong onsite Coulomb interaction leads to an S‐shape negative differential conductance in silicon. A large room temperature magnetoresistance (>10 3 % at 0.05 T) can be observed around the S‐shape negative differential conductance region.